Adjuvant chemotherapy with tegafur/uracil for more than 1 year improves disease‐free survival for low‐risk Stage II colon cancer. Issue 9 (September 2016) - Hu, Je‐Ming; Chou, Yu‐Ching; Wu, Chang‐Chieh; Hsiao, Cheng‐Wen; Lee, Chia‐Cheng; Chen, Chun‐Ting; Hu, Sheng‐I; Liu, Wei‐Tin; Jao, Shu‐Wen
Abstract : Background : It is uncertain whether adjuvant chemotherapy (CMT) improves survival in patients with low‐risk Stage II colon cancer. We aimed to determine the disease‐free survival (DFS) and 5‐year overall survival (OS) of low‐risk Stage II colon cancer patients treated with adjuvant tegafur/uracil (UFUR). Methods : From January 2004 to December 2011, the follow‐up status of 278 low‐risk Stage II colon cancer patients who underwent surgery in a single medical center was retrospectively analyzed. These patients were divided into three groups based on whether they received adjuvant CMT with UFUR, adjuvant CMT with 5‐fluorouracil, or surgery alone. DFS and 5‐year OS curves were calculated using Kaplan–Meier survival analysis and Cox proportional hazards regression. Results : In the study population, including 278 low‐risk Stage II colon cancer patients with a mean age of 68.28 ± 13.01 years, 132 (47.5%) received adjuvant CMT with UFUR, 49 (17.6%) received adjuvant CMT with 5‐fluorouracil, and 97 (34.9%) underwent radical surgery alone. At 5 years, the adjusted DFS and OS of low‐risk Stage II colon cancer patients were 85.5% and 81.8%, respectively, in the surgery alone group and 97.9% and 96.2%, respectively, in the surgery plus UFUR > 12 months group ( p = 0.004 and p = 0.098, respectively). In multivariate analysis, CMT with UFUR for more than 12 months increased DFS over surgery alone. There was no statistical difference in the 5‐year OS. Conclusion : Adjuvant CMT treatment of low‐risk Stage II colon cancer patients with UFUR for more than 12 months following surgery improves DFS over surgery alone.